2023
DOI: 10.1021/acsapm.2c02155
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Postprocessing Dimensional Change of Injection-Molded Products Composed of Poly(lactic acid) and Poly(vinyl alcohol)

Abstract: The present study revealed that an injection-molded product comprising poly(lactic acid) (PLA) and poly(vinyl alcohol) (PVAL) exhibited an anomalous dimensional change, i.e., expansion in the flow direction, after postprocessing annealing (around 2.9% expansion by annealing at 80−100 °C for 3 h). Although the crystallization of the PLA during cooling was not accelerated by the addition of PVAL, the PLA showed transcrystallization from the dispersed PVAL droplets, which were deformed in the flow direction, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Up to now, only a few studies have been reported on the orientation growth during annealing to the best of our knowledge. 48,49 A full-wave plate was inserted into the POM, which added 530 nm to the optical pathlength, to confirm the molecular orientation in the PLA/EBHS strands, as shown in Figure 13. The POM images revealed that the color of the strand before annealing was blue.…”
Section: Structure Of Extruded Strandsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, only a few studies have been reported on the orientation growth during annealing to the best of our knowledge. 48,49 A full-wave plate was inserted into the POM, which added 530 nm to the optical pathlength, to confirm the molecular orientation in the PLA/EBHS strands, as shown in Figure 13. The POM images revealed that the color of the strand before annealing was blue.…”
Section: Structure Of Extruded Strandsmentioning
confidence: 99%
“…[42][43][44][45][46][47] Although this is a severe problem in industry, almost no study has been performed to control the structure and dimensional change during annealing from a scientific point of view, except for a few studies reported recently. 48,49 It was found that PLA with an appropriate shear history showed chain orientation during post-process annealing, 48 that is, molecular orientation increased, not relaxed. Moreover, injectionmolded products of PLA containing a low-molecular-weight poly(vinyl alcohol) (PVA) 49 exhibited anomalous dimensional changes, that is, expansion in the flow direction and increased molecular orientation during post-process annealing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(lactic acid) (PLA), derived from renewable resources, has attracted widespread attention 1,2 . As an industry front‐running biodegradable polymer, PLA has been extensively applied in various fields, such as packaging films, 3 molded products, 4 3D‐printing, 5 and textiles 1 . Especially, PLA fibers have the potential as an alternative to the used petroleum‐based fibers 6,7 .…”
Section: Introductionmentioning
confidence: 99%